Cervical lymph node hyperplasia on [18F]-fluorodeoxyglucose positron emission tomography/computed tomography scan after treatment of children and adolescents with malignant lymphoma. Issue 7 (July 2015) - Hu, Ying-Ying; Zhang, Xu; Long, Wen; Lin, Xiao-Ping; Zhang, Ya-Rui; Li, Yuan-Hua; Xiao, Zi-Zheng; Zheng, Rong-Liang; Liang, Pei-Yan; Fan, Wei
Highlights: Cervical lymph node hyperplasia is a benign processes. Lymph node hyperplasia found in treated children and adolescents with lymphoma. We define imaging manifestations of cervical lymph node hyperplasia in PET/CT. Awareness of lymph node hyperplasia avoid invasive procedures and over-treatment. Abstract: Purpose: To define imaging manifestations and clinical prognosis of cervical lymph node hyperplasia using [ 18 F]-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) scanning after treatment of children and adolescents with malignant lymphoma. Methods: Children and adolescent patients with malignant lymphoma who had high FDG uptake in their cervical lymph nodes via PET/CT after treatment, which was not due to tumor recurrence or residue, were retrospectively analyzed. Results: Twenty-seven patients with a median age of 12 years were included; 11 had Hodgkin's disease and 16 had non-Hodgkin's lymphoma. The time from PET/CT scan to completion of therapy was 1–36 months, 85.2% (23/27) of which took place within 12 months. Three patients had confirmed lymph node follicular hyperplasia by biopsy, while all 27 patients achieved disease-free survival during the follow-up period. The maximum standardized uptake values (SUVmax ) of cervical lymph nodes were 2.2–16.2 and the maximum short axis ranged from 0.3 to 1.2 cm. Cervical lymph node hyperplasia was noted in neck levels I–V, and neck level II bilaterally had the highest incidence (100%). Bilateral cervical lymph node hyperplasia was symmetrical in terms of both the SUVmax and affected locations. Thymic hyperplasia and nasopharyngeal lymphoid hyperplasia were both observed in 24 patients (88.9%). There was no relationship in terms of the SUVmax between cervical lymph nodes and thymic tissue, cervical nodes or nasopharyngeal lymphoid tissue. Conclusion: Cervical lymph node hyperplasia with high FDG uptake on PET/CT scans found after treating children and adolescents with malignant lymphoma can be benign processes. Awareness of this possibility may help avoid invasive procedures and over-treatment.